AB0834 Acute Calcium Pyrophosphate Crystal Arthritis as A Cause of Sudden Onset of Fever and Arthritis in Geriatric Patients. (15th July 2016) - Yamamura, Y.; Fujita, K.; Shibutou, N.; Ueno, A.; Yamamura, M.
Abstract : Background: Calcium pyrophosphate (CPP) deposition may give rise to clinical presentations that mimic septic arthritis, polyarticular inflammatory arthritis or osteoarthritis. Of 4 different presentations 1), acute CPP crystal arthritis crystal arthritis, also known as pseudogout, is characterized by sudden attacks of arthritis frequently with systemic inflammatory features such as fever. Objectives: To determine clinical findings of patients with acute CPP crystal arthritis who was hospitalized due to fever of unknown origin or developed during hospitalization from 2011 to 2015. Methods: Patients were diagnosed as having acute CPP crystal arthritis according to the diagnostic criteria proposed by McCarty DJ 2) and classification of clinical presentations proposed by EULAR recommendation 1) . Results: We enrolled 26 patients with acute CPP crystal arthritis who were classified as described above, including 9 males and 17 females. All patients presented acute attacks of arthritis. Eight patients were hospitalized due to high fever; and others were for infections in 8 patients, strokes in 6, malignancies in 2 and other medial illnesses in 4, followed by arthritis or fever. The median age at diagnosis was 83.5 years (range 69–102). Fever (>37.5°C) developed in 17 patients and the mean CRP level (± SD) was 14.6±7.2 mg/dL (2.08 - 28.88; n=23). Ten patients were polyarticular or oligoarticular while 16 patients were monoarticular; and affected joints included knee joints in 18 patients, wrist in 6, ankle in 6, elbow in 3, shoulder in 2, cervical in 2, and finger in 2. CPP crystals were demonstrated in synovial fluids in 12 of 15 patients with arthrocentesis. The presence of CPPD deposition-related arthropathy including chondrocalcinosis was found in 24 patients by radiographic studies. All patients responded well to treatment including non-steroidal anti-inflammatory drugs (n=16), joint aspiration and rest (n=5), oral colchicine (n=3), intraarticular injection of glucocorticoids (n=3) and parenteral glucocorticoids (n=2; prednisolone 30 mg/day). Conclusions: The results indicates that acute CPP crystal arthritis develops in not rarely the geriatric population over 75 years of age, often leading to sudden onset of fever and disability. It should be noted that these attacks are often provoked by severe medical diseases such as infections and strokes. References: Zhang W, et al. European League Against Rheumatism recommendations for calcium pyrophosphate deposition. Part I: terminology and diagnosis. Ann Rheum Dis 2011;70:563–70. McCarty DJ. Crystals and arthritis. Dis Mon 1994;255–99. Disclosure of Interest: None declared